Reactivando las cadenas de los pinares en Las Segovias - Parrili, M.; Kaimowitz, D. (Nitlapan Institute, DFID and CIFOR, 2000)
This paper analyses the institutions and producers involved in pine production in Nueva Segovia, Nicaragua and the problems they face. It also presents the main findings and recommendations of a Study Tour conducted in the municipalities of Dipilto, Santa Clara, Jalapa, Ocotal, and Estel in May, 2000, sponsored by CIFOR, the World Bank, the Inter-American Development Bank, and the Nitlapan Institute. Particular attention is given to the role of municipal governments and processing industries.